Muhammad Sofwan wins UMPSA Chancellor’s Award - Nor Salwana, Mohammad Idris (UMPSA, 2024)
GAMBANG, 26 October 2024 – Muhammad Sofwan Sapiyan, 24, an outstanding graduate from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), has proven that a strong family ecosystem is the key to his academic success.